An exploratory study on Minangkabau local knowledge and information literacy for sustainability development in Agam district, Indonesia / Elva Rahmah - -, Elva Rahmah (2024)
Local knowledge is found in communities and consists of a set of accumulated experiences that provide information regarding a community's cultural and behavioural characteristics. Access to this information enables everyone within the community to have equal rights to economic resources and access to basic services, which ultimately leads to the sustainable development of individuals, communities and nations. Indonesia is known for consisting of more than 300 ethnographic groups and has a wealth of local knowledge that attracts policymakers and research institutions and one well-known local knowledge comes from a local community is from Minangkabau community. However, studies found that local knowledge, which has historically been transmitted from generation to generation by word of mouth, is at risk of being lost, and the information contained in local knowledge is still not recorded and managed efficiently. Information literacy is one of the major pre-requisites for sustaining local knowledge and cultural heritage, as an individual depends on information to survive in society. The implication is that diverse strategies must be employed to facilitate the acquisition of information literacy in local knowledge by the Minangkabau community so that sustainable development goals become realities at both individual and national level. Therefore, this research aims to explore Minangkabau local knowledge practices and information literacy in Agam district, Indonesia, for sustainability development. Mixedmethods approach was conducted sequentially, with qualitative approach as dominant. The first stage of quantitative instruments was distributed to the Minangkabau community and received 384 respondents through a purposive sampling technique and data was analysed using Statistical Package for the Social Sciences (SPSS) version 26 to identify the level of local knowledge and information literacy among Minangkabau communities. The next phase of this research used qualitative instruments with 12 leaders, namely: traditional leaders, religious leaders, and community leaders and analysis done through NVIVO 14. The results from the quantitative findings show that the highest mean value is explicit knowledge through combination, 4.35, where Minangkabau community gained local knowledge from tacit and explicit knowledge. As for the qualitative findings, the roles of Minangkabau community leaders are crucial in managing and protecting local knowledge with the utilization of technology. Further statistical analysis also showed that there is a correlation between local knowledge and information literacy among Minangkabau community. The research also found that the challenges of local knowledge are oral tradition, information storage media, modernization, and knowledge owner. This research makes a recommendation to policymakers and other relevant authorities with a proposed framework for managing local knowledge, which cover input, process, and outcome that will strengthen local knowledge for future generations for the appreciation of traditional knowledge and generate the growth of the Minangkabau community's socio-economic and knowledge development. This research also supports the Sustainable Development Goals agenda by UNESCO 2030, especially SDG 11: sustainability of cities and communities; SDG 1: no poverty; and SDG 4: quality education. iv